Fabrication and characterization of glass ionomer cement using alumino-silicate-fluoride based-glass ceramics from waste resources - Abdul Jalil, Rohaniah (2021)
The success of Glass Ionomer Cement (GIC) innovations in dentistry has attracted interest among researchers over the last 40 years. However, there is limited research regarding the usage of Alumino-Silicate-Fluoride (ASF) based glass ceramics derived from waste resources in the fabrication of GIC. This research's main focus is to fabricate GIC using ASF-based glass ceramics derived from waste resources of clam shell (CS) and soda lime silica (SLS) glass. Two batches of ASF glass ceramics sample labeled as Batch 1 (B1) and Batch 2 (B2) were prepared following the empirical formula of [(x)CS∙(45-x) SLS∙15CaF2∙20P2O5∙20Al2O3] where x = 5 and 20 (wt.%). Both batches have a different composition in SLS and CS which will be studied in this work. The ASF based glass ceramics were synthesized by using conventional melt quenching techniques. Then, GIC was fabricated using three main components of ASF based glass ceramics, polyacrylic acid (PAA) and water. The thermal, physical, structural, chemical and mechanical properties of ASF glass ceramics and GIC had been determined by using X-ray fluorescence (XRF), differential scanning calorimetry (DSC), density measurement, X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) and compressive strength test (CST). The XRF showed the largest percentage of SLS glass elements is silicon dioxide (SiO2) around 79 % while CS has 99.52 % of calcium oxide (CaO), which makes them suitable as a source for ASF glass composition. The DSC showed glass transition temperature, Tg around 764-785 °C and crystallization temperature, Tc around 918 - 986 °C. The density measurement of GIC showed an increasing pattern from 600 - 800 °C. Then, the density decreased at a high sintering temperature of 1000 - 1200 °C. This is due to the formation of anorthite (Ca(Al2Si2O8) and mullite (Al5SiO9.5) at high sintering temperatures. The XRD analysis revealed fluorapatite (Ca5(PO4)3F) as a major phase in GIC samples which decomposed into anorthite and mullite at 1000 - 1200 °C. Next, FTIR revealed the presence of CO3 group, Si-O-Si, P-O, crystalline phosphate, CH3 and O-H band which indicates the structure of the glass matrix and the crystallization of the GIC sample. The uniform spherical microstructure was observed, which converted to a coarse structure at high sintering temperatures in FESEM due to devitrification. The EDX analysis revealed a Ca/P ratio obtained around 1.17 - 3.49 is suitable for body implantation. CST has the same pattern as the density measurement of GIC. The decline of the pattern was attributed to the decomposition of fluorapatite into mullite and anorthite. A selected sample of B1 GIC at 800 °C and 28 days was discovered as an optimum result due to the highest CST value achieved, 82.03 MPa. In conclusion, GIC shows a potential candidate for clinical applications in dentistry as their mechanical properties completed the requirement for dental application (70 MPa) following the International standard organization (ISO) 9917.